Statistical reconstruction of daily precipitation and temperature fields in Switzerland back to 1864 - L. Pfister; L. Pfister; S. Brönnimann; S. Brönnimann; M. Schwander; F. A. Isotta; P. Horton; P. Horton; C. Rohr; C. Rohr (Climate of the Past, 2020)
Spatial information on past weather contributes to better understanding the processes behind day-to-day weather variability and to assessing the risks arising from weather extremes. For Switzerland, daily resolved spatial information on meteorological parameters is restricted to the period starting from 1961, whereas prior to that local station observations are the only source of daily long-term weather data. While attempts have been made to reconstruct spatial weather patterns for certain extreme events, the task of creating a continuous spatial weather reconstruction dataset for Switzerland has so far not been addressed. Here, we aim to reconstruct daily high-resolution precipitation and temperature fields for Switzerland back to 1864 with an analogue resampling method (ARM) using station data and a weather type classification. Analogue reconstructions are post-processed with an ensemble Kalman fitting (EnKF) approach and quantile mapping. Results suggest that the presented methods are suitable for daily precipitation and temperature reconstruction. Evaluation experiments reveal excellent skill for temperature and good skill for precipitation. As illustrated with the example of the avalanche winter of 1887/88, these weather reconstructions have great potential for various analyses of past weather and for climate impact modelling.